Designing Integrated Patient Safety Incident Reporting with Hospital Information System - Sutejo Sutejo; Agung Budi Prasetijo; Farid Agushybana (Universitas Aisyah Pringsewu, 2021)
Incident reporting systems are designed to obtain patient safety information that is used for organizational and individual learning. Currently, the recording of patient safety incident reports has been facilitated by the ministry of health through the implementation of the quality of health facilities, especially for incidents with unexpected events (KTD) or sentinels. Incident recording in hospitals is still very weak, so incident data cannot be analyzed properly and correctly to improve the quality of hospital services. This study aims to design an Integrated Patient Safety Incident Reporting Information System (SIPIKAT). The design of SIPIKAT uses the Systems Development Life Cycle (SDLC) method with the Framework for the Application of System Techniques (FAST). In-depth interviews and Focus Group Discussions (FGD) were conducted to obtain the necessary data. This web-based SIPIKAT is designed using PHP 5.6 and Javas-script, MySQL database, and Apache webserver. SIPIKAT integration with Hospital Information System (SIMRS) via web service to retrieve patient identity data including name; date of birth and medical record number. The output is in the form of incident report information and risk grading to be followed up. Conclusion SIPIKAT Research is easy to use and generates information on risk aggregation required for follow-up. Abstrak: Sistem Pelaporan Insiden Keselamatan Pasien dirancang untuk memperoleh informasi tentang keselamatan pasien yang digunakan untuk pembelajaran organisasi dan individu. Saat ini, pencatatan laporan insiden keselamatan pasien telah difasilitasi oleh kementerian kesehatan melalui penerapan mutu fasilitas kesehatan, terutama untuk insiden dengan kejadian tak terduga (KTD) atau sentinel. Pencatatan insiden di rumah sakit masih sangat lemah, sehingga data insiden tidak dapat dianalisis dengan baik dan benar untuk meningkatkan kualitas pelayanan rumah sakit. Penelitian ini bertujuan untuk merancang Sistem Informasi Pelaporan Insiden Keselamatan Pasien Terpadu (SIPIKAT). Perancangan SIPIKAT menggunakan metode Systems Development Life Cycle (SDLC) dengan Framework for the Application of System Techniques (FAST). Wawancara mendalam dan Focus Group Discussion (FGD) dilakukan untuk mendapatkan data yang diperlukan. SIPIKAT berbasis web ini dirancang dengan menggunakan PHP 5.6 dan Javas-cript, database MySQL, dan web server Apache. Integrasi SIPIKAT dengan Sistem Informasi Rumah Sakit (SIMRS) melalui web service untuk mengambil data identitas pasien termasuk nama; tanggal lahir dan nomor rekam medis. Outputnya berupa informasi laporan insiden dan risk grading untuk ditindaklanjuti. Kesimpulan Penelitian SIPIKAT mudah digunakan dan menghasilkan informasi tentang agregasi risiko yang diperlukan untuk tindak lanjut.